Indicators System Improvement to Assess the Innovative Activity of Economic Entities, Taking into Account the Compliance with the Strategic Goals of Socio-Economic Developmen - T. V. Pogodina; N. M. Abdikeev; Yu. S. Bogachev (Учёт. Анализ. Аудит, 2019)
In the society today, as well as in public administration and economic entities of the Russian Federation there is an awareness of the need to activate the innovation process and assess its quality. In addition, global challenges require the implementation of foresight management mechanisms aimed at forecasting technological development in the conditions of Russian reality. However, the existing system of indicators that is used in Russian practice does not fully meet the needs of the state and society in assessing innovation. The article proposes a Balanced system of indicators for assessing innovation activity (SSPOID) of economic entities, which is designed to combine the past and the present with the prospects of development, the objective function of which is to maximize the increment of the market value of the economic entity, taking into account the mission and strategic priorities of each particular company. SSPOID includes indicators, which are divided into nine groups that characterize the socio-economic development of the economic entity, human capital, financial condition, competitiveness, technology, competitiveness in the labor market, investment, innovation and sources of innovative development. The analysis of the development of industrial production in the Russian Federation for the period of 2011–2016 allowed to determine the strengths and weaknesses in innovation. The strategies of innovative development of a number of production companies (ALROSA, PJSC «NC “Rosneft”, JSC “United shipbuilding company”, JSC “BALTIKA”) were analyzed. The main areas of their innovation activities are as follows: improving energy efficiency, focus on strategic technology, the digitalization of production, the implementation of environmental innovations, improving production security, import substitution. The necessity in the creation of the integrated industrial and production complex, which will be optimum from the point of view of satisfaction of consumers’ needs for production, is justified. In the framework of the integrated industrial complex, the rationale for its focus on creating and maximizing the increment of the network added value is proved.